2011
DOI: 10.4049/jimmunol.1003585
|View full text |Cite
|
Sign up to set email alerts
|

A Point Mutation in the Amino Terminus of TLR7 Abolishes Signaling without Affecting Ligand Binding

Abstract: TLR7 is the mammalian receptor for ssRNA and some nucleotide-like small molecules. We have generated a mouse by N-nitrose-N′-ethyl urea mutagenesis in which threonine 68 of TLR7 was substituted with isoleucine. Cells bearing this mutant TLR7 lost the sensitivity to the small-molecule TLR7 agonist resiquimod, hence the name TLR7rsq1. In this work, we report the characterization of this mutant protein. Similar to the wild-type counterpart, TLR7rsq1 localizes to the endoplasmic reticulum and is expressed at norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 58 publications
2
24
0
Order By: Relevance
“…Of note, the sites identified here do not appear critical for ligand binding. Earlier studies showed a general promiscuity of TLR7 for both RNA and DNA (37) and in an ORN pull-down assay we found TLR7 binding was stronger for activating vs. non-activating ORN, but not altogether abrogated (19), indicative of a basal level of (non-specific) binding for nucleic acids. Similarly to TLR9 (10, 38) RNA ORN binding by TLR7 and TLR8 thus appears to be relatively non-specific with ligand recognition being a separate event dependent on the presence of activation determinants (e.g.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Of note, the sites identified here do not appear critical for ligand binding. Earlier studies showed a general promiscuity of TLR7 for both RNA and DNA (37) and in an ORN pull-down assay we found TLR7 binding was stronger for activating vs. non-activating ORN, but not altogether abrogated (19), indicative of a basal level of (non-specific) binding for nucleic acids. Similarly to TLR9 (10, 38) RNA ORN binding by TLR7 and TLR8 thus appears to be relatively non-specific with ligand recognition being a separate event dependent on the presence of activation determinants (e.g.…”
Section: Discussionsupporting
confidence: 54%
“…Indeed rsq2 peritoneal macrophages failed to respond to R848 (Fig. 7A,B) like the ‘functionally null’ Tlr7 strain rsq1 (mutation T68I; Ref. (19)).…”
Section: Resultsmentioning
confidence: 95%
“…3), the role of this receptor in RNA vaccine activity was further evaluated. We compared the cytokine pattern of human PBMCs (hPBMCs) stimulated with a TLR7 agonist, the single-stranded ribonucleotide R0006 (9), with the pattern induced with SAM (RNA) or an amplification-deficient version of SAM (DRNA). Both of the molecules were delivered with DOTAP, because this transfection reagent delivers RNA to the endosomes (26), where TLR7 is localized.…”
Section: Mapping Of Endosomal Rna Sensors Highlights the Role Of Tlr7mentioning
confidence: 99%
“…In addition, we used a mouse genetic mutant (TLR7 rsq1 ) and KO models (MyD88 and TLR3) to elucidate the importance of the TLR7 pathway. TLR7 rsq1 mice contain a point mutation within TLR7 that blocks the ability of the receptor to respond to ssRNA and smallmolecule agonists (9). MyD88 is a key signaling adapter downstream of some TLRs including TLR7.…”
Section: Mapping Of Endosomal Rna Sensors Highlights the Role Of Tlr7mentioning
confidence: 99%
See 1 more Smart Citation